Motivasi Belajar Siswa dalam Perspektif Ekologis: Kajian atas Peran Lingkungan Sekolah, Aktivitas Belajar, Perhatian Orang Tua, dan Sumber Belajar - Darmawan, Didit; Kamalia, Dinna (Lembaga Intelektual Muda (LIM) Maluku, 2026)
This study aims to analyse the role of the school environment, learning activities, parental attention, and the availability of learning resources in shaping students’ learning motivation through a literature review approach. The study employed a qualitative method using thematic content analysis of academic literature, comprising journal articles and books relevant to the topics of learning motivation and educational psychology, published between 2000 and 2015. The analysis was conducted through the stages of source collection, coding of key concepts, thematic grouping, and drawing conclusions based on the interrelationships between factors. The results of the study indicate that a conducive school environment, both physically and socially, creates a sense of security and encourages student engagement in learning. Meaningful and challenging learning activities contribute to the development of intrinsic motivation through experiences of competence and positive social interaction. This study concludes that students’ motivation to learn does not exist in isolation, but is shaped by the synergy of environmental, pedagogical and family factors, and provides a conceptual basis for the development of more holistic educational practices.